EFEK KOMUNIKASI ANTAR PERSONA PIMPINAN PONDOK (KYAI) PESANTREN AL-HIKMAH TERHADAP PERILAKU SANTRI (Studi Pondok Pesantren Al-Hikmah Kecamatan Kedaton) - Aliyandi Aliyandi (IAIN Padangsidimpuan, 2018)
Communication between people is one of the communication techniques that is always used by everyone. With the process of interpersona communication expected the behavior of a person can change according to what the communicator wants.Islamic boarding school is one of the Islamic education institutions which has the aim of preparing the ummah cadre who has a noble character. And one of the characteristics is having good behavior.The purpose of this study was to determine the pattern of communication between persona which was determined by the leadership of the boarding school (Kyai) of the pesantren and from the communication pattern towards the behavior of students.The method used in this study is analytical descriptive. The sample of this study was taken as much as 10% of the study population totaling 250 people who were students who lived in the Al-Hikmah Way Halim cottage in Kedaton sub-district, Bandar Lampung city.Data collection techniques conducted by the author are literature studies, field studies, interviews, documentation, and observation. While the data analysis used is qualitative analysis techniques. From the results of the study showed that communication between the persona of the head of the cottage (kyai) of the Al-Hikmah Islamic Boarding School Way Halim Bandar Lampung had a positive effect on the behavior of students. This can be seen from changes in behavior that occurs in students after attending education at the boarding school, increasing discipline, worship and interaction patterns of students in the boarding school.